Os efeitos da pandemia da COVID-19 na captação e fidelização dos doadores de sangue do Centro de Hematologia e Hemoterapia “José Scaff” – Campo Grande, MS - Araujo Filho, Edivaldo Jose de (2022)
Blood donation is a gesture of solidarity, a voluntary and altruistic act of global interest, and its lack is a public health problem. The coronavirus pandemic has impacted health systems around the world in sever always and brought the need to implement a series of interventions to reduce the transmission of the virus and stop its rapid evolution. The research aimed to analyze the effects of the Covid-19 pandemic in the recruitment and loyalty of blood donors at the Center for Hematology and Hemotherapy “José Scaff” - Campo Grande, MS. This is a cross-sectional study, with a quantitative and analytical approach, which used secondary data collected through the institution's database. The number of records of blood donors for the period 2016 to 2020 was collected. The results show that there was no difference between the period 2016 to 2019 and that of 2020, in relation to spontaneous, replacement, autologous donations, first donation and repetition. On the other hand, there was a significant increase in 2020, when compared with period 2016 to 2019, in the amount of sporadic donations. Although more than 50% of the population of Mato Grosso do Sul is female, the percentage of female blood donors in 2020 was only 41.25%. In 2020 there was a decrease in donors aged between 18 and 29 years, in comparison with the same period 2016 to 2019. In addition, there was no difference between the period 2016 to 2019, with the year 2020, in the number of donors aged over 29 years. Overall, in the year 2020 there was a reduction of 5.3% in blood donations, compared with year 2019. However, the period 2016 to 2019 showed an annual increase in the number of donations, considering the trend of this growth, the year 2020 showed a reduction of 13.3% in the total number of blood donations, this is equivalent to 5500 blood bags that were not collected. The emergence of new diseases and emerging pandemics is a challenge for which Blood Centers must be aware and ready to quickly adopt measures that mitigate the impact on donor care and on the production of blood components and, consequently, on meeting the transfusion demand.